Involvement of nitric oxide in the gastroprotective effects of an aqueous extract of Pfaffia glomerata (Spreng) Pedersen, Amaranthaceae, in rats - Freitas, C. S.; Baggio, C. H.; Da Silva-Santos, J. E.; Rieck, L.; Santos, CAD; Junior, C. C.; Ming, Lin Chau [UNESP]; Cortez, DAG; Marques, MCA (Elsevier B.V., 2004)
The plants belonging to Pfaffia genus are used in folk medicine to treat gastric disturbances. This study examined the effects of an aqueous extract of Pfaffia glomerata (Spreng) Pedersen (AEP) on the gastrointestinal tract. Wistar rats were pretreated orally (p.o.) with the AEP (125, 250, 500 and 1000 mg.kg(-1)) before induction of ulcers by hypothermic restraint stress (HRS, 3 h restraint stress at 4 degreesC), ethanol (ET, 70%; 0.5 ml/animal; p.o.) or indomethacin (IND, 20 mg.kg(-1); s.c.). Control animals received water (C) or ranitidine (60 mg.kg(-1)) p.o. The AEP protected rats against HRS and ET-induced ulcers, but was not able to protect the gastric mucosa against IND-induced ulcers. When injected into the duodenal lumen, the AEP reduced total acidity and both basal and histamine-stimulated acid secretion in pylorus-ligated rats. In addition, gastric secretion from AEP-treated animals exhibited increased concentrations of nitrite and nitrate. Treatment of animals with L-NAME (120 mg.kg(-1), p.o.) prevented both the reduction of total acidity and the increase in NO, levels promoted by AEP treatment. In conclusion, AEP effectively protected the gastric mucosa and inhibited gastric acid secretion in rats, probably by involving the histaminergic pathway and an enhanced production of nitric oxide in the stomach. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: gastric secretion inhibition; Pfaffia glomerata; nitric oxide